10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
OBJECTIVE: The objective of this study is to provide a practical clinical summary for the effective management of anemia using vitamin B12, folic acid, and especially iron combined with erythropoietin (EPO), to facilitate the implementation of the Patient Blood Management (PBM) program in hospitals. DATA SOURCES: The review followed the PRISMA 2020 statement, and the protocol was registered in PROSPERO. A systematic literature search was conducted in the Cochrane Library, PubMed, PubMed Central, MEDLINE, EMBASE, EBSCO, and LILACS. STUDY SELECTION AND DATA EXTRACTION: Randomized controlled and observational studies were included, while selected reviews were used for contextual interpretation. Data were synthesized qualitatively within a practical clinical synthesis framework, and certainty of evidence was assessed using the GRADE approach. DATA SYNTHESIS: A total of 2495 records were identified, 156 articles underwent full-text review, and 43 studies were included. Across studies, therapy with vitamin B12, folic acid, and iron, as well as EPO, was associated with increased hemoglobin levels and reduced allogeneic transfusion requirements. Reported iron regimens included oral elemental iron at 60 to 120 mg/day and intravenous iron at 10 to 20 mg/kg/week, with maximum weekly doses ranging from 600 to 1000 mg, depending on formulation. Reported EPO regimens included 600 IU/kg/week administered intravenously or subcutaneously for moderate-to-severe anemia and 300 IU/kg/day in critical settings. Heterogeneity was observed in dosing strategies, timing, and routes of administration across studies. RELEVANCE TO PATIENT CARE AND CLINICAL PRACTICE: This review provides an evidence-informed clinical framework to support physicians, pharmacists, and nurses in the pharmacologic management of anemia. Synthesizing commonly reported strategies for intravenous iron and erythropoietin therapy facilitates the implementation of the first pillar of PBM and supports clinical decision-making. CONCLUSIONS: Iron and erythropoietin therapy were consistently associated with increased hemoglobin levels and reduced allogeneic transfusion requirements. The dosing regimens identified across studies provide a practical evidence-informed framework for anemia management within PBM programs.Systematic Review Protocol:CRD420261295920 (PROSPERO).